Negative plate for new energy battery and method for preparing negative plate

By using aluminum foil and specially made negative electrode slurry in the negative electrode sheet of lithium-ion battery, the limitations of existing negative electrode materials in terms of energy density, safety and cycle stability are solved, and high energy density, high power density and long cycles are achieved. Battery performance for life.

CN119480903AActive Publication Date: 2025-02-18南京宁嘉新材料科技有限公司
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411625091.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-18
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

Existing lithium-ion battery anode materials have limitations in terms of energy density, safety and charge and discharge rates. Especially in the applications of new energy vehicles and energy storage devices, it is necessary to develop high energy density, high power density and excellent safety. Negative electrode material with long cycle life.

Method used

The negative electrode sheet consists of aluminum foil and negative electrode slurry. The negative electrode slurry consists of lithium titanate, conductive modifier and interface stabilizer. The conductive modifier is prepared through specific polymerization reactions, and the interface stabilizer is passed through tripolymer cyanochloride and dichloride. Raw materials such as ethylamine, 4,7-dichloroquinoline and 2-methylpiperazine are prepared, which are used to improve conductivity and interface stability respectively.

Benefits of technology

It significantly improves the conductivity, structural stability and electrochemical properties of the negative electrode sheet, extends the cycle life of the battery, and improves the safety and charge and discharge rate of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005134525870000041
    Figure BDA0005134525870000041
Patent Text Reader

Abstract

The invention discloses a negative plate for a new energy battery and a method for preparing the negative plate, and belongs to the technical field of negative plate preparation. The negative electrode plate for the new energy battery is composed of an aluminum foil and negative electrode slurry, the negative electrode slurry is composed of the following components in parts by weight: 42-48 parts of lithium titanate, 6-10 parts of a conductive modifier, 5-12 parts of an interface stabilizer, 2-5 parts of a binder and 1-4 parts of N-methyl pyrrolidone, the interface stabilizer is prepared from 4, 4 '-(hexafluoroisopropenyl) diphthalic anhydride, 4, 4'-diaminodiphenyl ether, hydroxyl-terminated polycaprolactone, diphenylmethane diisocyanate, isophthaloyl hydrazine, acrylic acid and poly (3, 4-ethylenedioxythiophene)-polystyrene sulfonate, and the interface stabilizer is prepared from cyanuric chloride, diethylamine, 4, 7-dichloroquinoline and 2-methyl piperazine. The negative plate prepared by the method has excellent safety, conductivity and cycling stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of negative electrode sheet preparation, and in particular relates to a negative electrode sheet for a new energy battery and a method for preparing the negative electrode sheet. Background Art

[0002] With the urgent global demand for environmental protection and sustainable development, new energy battery technology has developed rapidly. As one of the mainstream technologies of new energy batteries, lithium-ion batteries have the advantages of high energy density, long cycle life, low self-discharge rate, no memory effect and environmental friendliness. They are widely used in electric vehicles, portable electronic devices and energy storage systems. However, traditional lithium-ion battery negative electrode materials, such as graphite, although they have stable cycle performance and good conductivity, have limitations in energy density, safety and charge and discharge rate. Especially with the rapid development of large-scale energy storage devices such as new energy vehicles and smart grids, the development of lithium-ion batteries with high energy density, high power density, excellent safety and long cycle life has become a hot research topic in the field of energy storage.

[0003] Patent CN 106848312 A discloses a modified porous graphene, a modified porous graphene negative electrode sheet and a preparation method thereof. The modified porous graphene of the invention is obtained by surface treatment of porous graphene and modification with an organic lithium compound, and then the modified porous graphene is combined with dry electrode processing technology to form a negative electrode sheet. By controlling parameters such as the specific surface area, particle size, pore size distribution, and surface functional group content of porous graphene, the modified porous graphene negative electrode material has the advantages of high coulomb efficiency and high rate, but the safety, conductivity and cycle stability of the negative electrode sheet prepared by this method still have room for improvement. Summary of the invention

[0004] The purpose of the present invention is to provide a negative electrode sheet for a new energy battery and a method for preparing the negative electrode sheet, so as to solve the technical problems of poor safety, conductivity and cycle stability of the negative electrode sheet in the prior art.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] The invention provides a negative electrode sheet for a new energy battery. The negative electrode sheet for the new energy battery is composed of aluminum foil and negative electrode slurry. The negative electrode slurry is composed of the following components in parts by weight: 42-48 parts of lithium titanate, 6-10 parts of a conductive modifier, 5-12 parts of an interface stabilizer, 2-5 parts of a binder, and 1-4 parts of N-methylpyrrolidone. The conductive modifier is prepared from 4,4'-(hexafluoroisopropylene) diphthalic anhydride, 4,4'-diaminodiphenyl ether, hydroxyl-terminated polycaprolactone, diphenylmethane diisocyanate, isophthalic acid hydrazide, acrylic acid and poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate, and the interface stabilizer is prepared from cyanuric chloride. 、 Diethylamine 、 The invention discloses a novel nanostructured carbon nanotube, which is prepared by using 4,7-dichloroquinoline and 2-methylpiperazine. The binder is composed of one or more of polyvinylidene fluoride, sodium polyacrylate, sodium alginate and sodium carboxymethyl cellulose.

[0007] Preferably, the method for preparing the conductive modifier comprises the following steps:

[0008] Q1: Add 4,4'-(hexafluoroisopropylene) diphthalic anhydride to a container containing N,N-dimethylacetamide, stir to dissolve, and then slowly add dropwise to the N,N-dimethylacetamide solution containing 4,4'-diaminodiphenyl ether. After reacting in an ice bath, stir and react at room temperature. After the reaction is completed, a light yellow liquid is obtained.

[0009] Q2: Add hydroxyl-terminated polycaprolactone to N,N-dimethylacetamide, heat under nitrogen atmosphere, then add diphenylmethane diisocyanate and dibutyltin dilaurate to react to obtain a prepolymer, then add isophthalic acid hydrazide to the prepolymer, react under nitrogen atmosphere, and obtain a polymer after the reaction is completed;

[0010] Q3: Add acrylic acid to distilled water, stir, then add ammonium persulfate and poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate, stir evenly, add sodium sulfite, heat and react to obtain a gel;

[0011] Q4: Add terephthalaldehyde to N,N-dimethylacetamide, add light yellow liquid and polymer substance under stirring condition, heat and stir to obtain a mixed solution, stir and mix the mixed solution with gel to obtain a conductive modifier.

[0012] In the above process, firstly, amino-terminated polyamic acid is prepared by using 4,4'-(hexafluoroisopropylene) diphthalic anhydride and 4,4'-diaminodiphenyl ether, and then polyurethane-urea is prepared by using hydroxyl-terminated polycaprolactone, diphenylmethane diisocyanate and isophthalic acid hydrazide as raw materials, and then acrylic acid is used as the basic material, doped with poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate, and an ammonium persulfate-sodium sulfite redox initiation system is used to prepare a gel, and polyamic acid segments are introduced into the polyurethane-urea with polycaprolactone as the main chain, and the rigid polyamic acid segments are aggregated to form a rigid hard phase structure, and the polycaprolactone segments cross-linked by hydrogen bond arrays are further cross-linked to form a double-cross-linked reversible cross-linked body, and then the conductive gel is incorporated into the reversible cross-linked body to obtain a conductive modifier.

[0013] Preferably, in Q1, the molar ratio of 4,4'-(hexafluoroisopropylene) diphthalic anhydride and 4,4'-diaminodiphenyl ether is (0.25-0.5):(0.3-0.6), the ice bath reaction time is 4-6h, and the stirring reaction time is 10-12h; in Q2, the average molecular weight of the hydroxyl-terminated polycaprolactone is 2000Da, and the molar ratio of the hydroxyl-terminated polycaprolactone, diphenylmethane diisocyanate, dibutyltin dilaurate and isophthalic acid hydrazide is (0.5-1):(1-2):(0.016-0.02):(0.62-1.25), the heating temperature is 80-90°C, the reaction time is 20-24h, and the reaction time under nitrogen atmosphere is 22-24h.

[0014] Preferably, in Q3, the usage ratio of acrylic acid, distilled water, ammonium persulfate, poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate and sodium sulfite is (6-10) mL: (20-25) mL: (0.025-0.03) g: (0.4-0.6) mL: (0.092-0.128) g, the heating reaction temperature is 40-50°C, and the reaction time is 10-15 min; in Q4, the usage ratio of terephthalaldehyde, N,N-dimethylacetamide, light yellow liquid, polymer substance and gel is (0.32-0.64) g: (25-50) mL: (1.4-2.8) g: (12.9-25.8) g: (0.3-0.5) g, the heating and stirring temperature is 90-110°C, the stirring time is 10-12 h, and the stirring and mixing time is 2-3 h.

[0015] Preferably, the method for preparing the interface stabilizer comprises the following steps:

[0016] S1: Add cyanuric chloride to a container containing tetrahydrofuran, stir to dissolve, dissolve diethylamine in tetrahydrofuran, slowly add it dropwise to the container, stir to mix, add potassium carbonate, react at low temperature, add distilled water to quench the reaction, extract, dry, and purify to obtain intermediate 1;

[0017] S2: Add 4,7-dichloroquinoline and 2-methylpiperazine to anhydrous ethanol, stir to dissolve, heat to reflux, and after the reflux is completed, perform vacuum distillation and purification to obtain intermediate 2;

[0018] S3: Add intermediate 2 to 1,4-dioxane, mix well, add potassium carbonate and intermediate 1, stir at room temperature, filter, distill under reduced pressure, and purify to obtain an interfacial stabilizer.

[0019] In the above process, the synthesis reaction formula of the interface stabilizer is as follows:

[0020]

[0021] The results of mass spectrometry analysis of intermediate 1 were: m / z: 220.03 (100.0%), 222.03 (64.3%), 224.02 (10.2%), 221.03 (9.2%), 223.03 (4.9%); the results of mass spectrometry analysis of intermediate 2 were: m / z: 261.10 (100.0%), 263.10 (32.1%), 262.11 (15.3%), 264.10 (5.2%), 262.10 (1.1 %), 263.11 (1.1%); the results of mass spectrometry analysis of the interfacial stabilizer were: m / z: 445.15 (100.0%), 447.15 (64.0%), 446.16 (23.0%), 448.16 (14.9%), 449.15 (10.6%), 447.16 (3.1%), 450.15 (2.6%), 446.15 (2.6%), 448.15 (1.7%), 449.16 (1.6%).

[0022] Preferably, in S1, the usage ratio of cyanuric chloride, diethylamine and potassium carbonate is 1g:(0.438-0.53)g:(1.8-2.1)g, the low-temperature reaction temperature is -10 to -15°C, the time is 1-2h, the extraction is carried out with ethyl acetate, and the reaction is dried with anhydrous magnesium sulfate.

[0023] Preferably, in S2, the dosage ratio of 4,7-dichloroquinoline, 2-methylpiperazine and anhydrous ethanol is 1g:(10-12.5)g:(20-25)mL, the heating reflux temperature is 70-80°C, the time is 5-7h, and the purification is carried out after adding silica gel powder. The eluent is a mixed solution of dichloromethane and methanol in a volume ratio of 10:1.

[0024] Preferably, in S3, the molar ratio of intermediate 2, 1,4-dioxane and intermediate 1 is (0.8-1.2):(0.8-1.2):(0.9-1.2), the stirring time at room temperature is 12-16 hours, and purification is carried out after adding silica gel powder. The eluent is a mixed solution of ethyl acetate and petroleum ether in a volume ratio of 5:1.

[0025] Preferably, the method for preparing the negative electrode sheet for new energy batteries comprises the following steps:

[0026] Step 1: Add a binder to N-methylpyrrolidone, then add lithium titanate, add a conductive modifier and an interface stabilizer after magnetic stirring, and continue magnetic stirring to obtain a negative electrode slurry;

[0027] Step 2: Evenly coat the negative electrode slurry on the aluminum foil and vacuum dry it to obtain a negative electrode sheet.

[0028] Preferably, in the step 1, the magnetic stirring time is 3-5 hours, and the continued magnetic stirring time is 10-12 hours; in the step 2, the vacuum drying temperature is 80-90°C, the vacuum degree is 0.1-0.2MPa, and the drying time is 10-12 hours.

[0029] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0030] 1. The present invention first uses 4,4'-(hexafluoroisopropylene) diphthalic anhydride, 4,4'-diaminodiphenyl ether, hydroxyl-terminated polycaprolactone, diphenylmethane diisocyanate, isophthalic acid hydrazide, acrylic acid and poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate as raw materials to prepare a conductive modifier, and then uses cyanuric chloride to 、 Diethylamine 、 An interface stabilizer is prepared using 4,7-dichloroquinoline and 2-methylpiperazine as raw materials. During the preparation of the negative electrode sheet, the addition of a conductive modifier can make lithium titanate have high conductivity while having safety performance. The addition of the interface stabilizer can provide abundant ion transmission channels, increase the current density and cycle time of the battery, and increase the service life of the battery.

[0031] 2. The present invention can effectively improve the conductivity, structural stability and electrochemical performance of the negative electrode sheet by adding a conductive modifier to the preparation process of the electrode sheet. The poly (3,4-ethylenedioxythiophene) -polystyrene sulfonate introduced in the conductive modifier can construct an efficient conductive network in the negative electrode sheet, so that electrons can migrate quickly, significantly reduce resistance and reduce battery polarization. At the same time, the rigid polyamic acid segment and the cross-linked polycaprolactone segment together constitute a stable network structure, which effectively withstands the stress during ion embedding / de-embedding, slows down the volume change of the negative electrode material, and maintains the integrity and performance stability of the negative electrode sheet. In addition, the conductive modifier can also improve the interface contact between the negative electrode sheet and the electrolyte, promote the transmission and diffusion of ions, and the infiltration and penetration of the electrolyte, thereby reducing the diffusion resistance of ions, improving the utilization rate of ions and the cycle stability of the battery.

[0032] 3. The present invention can effectively improve the interface stability of the negative electrode sheet by adding an interface stabilizer to the negative electrode sheet, and can also optimize the ion transmission of the negative electrode sheet. The nitrogen atoms contained in the interface stabilizer can form coordination bonds or chemical bonds with the metal atoms on the surface of the negative electrode sheet, thereby enhancing the polarity of the surface of the negative electrode sheet and making the interaction between it and the electrolyte more stable. Through chemical bonds and, the interface stabilizer can be firmly adsorbed on the surface of the negative electrode sheet to form a dense protective layer, which can effectively prevent the harmful substances in the electrolyte from corroding the negative electrode sheet and extend the service life of the negative electrode sheet. The presence of the interface stabilizer can also reduce the interfacial tension between the negative electrode sheet and the electrolyte, making the contact between the negative electrode sheet and the electrolyte closer and smoother, reducing unnecessary interface reactions and energy losses, and helping to improve the cycle stability and safety of the battery; and the interface stabilizer can improve the microstructure of the surface of the negative electrode sheet, form a channel that is conducive to ion transmission, reduce the transmission resistance of the ions, make it easier to diffuse and migrate inside the negative electrode sheet, and enhance the charge and discharge rate and capacity utilization of the battery. DETAILED DESCRIPTION

[0033] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] Example 1: This example discloses a method for preparing a conductive modifier, comprising the following steps:

[0035] Q1: Add 1.38g of 4,4'-(hexafluoroisopropylene) diphthalic anhydride to a container containing 7.5mL of N,N-dimethylacetamide, stir to dissolve, and then slowly add dropwise to a 6mL N,N-dimethylacetamide solution containing 0.75g of 4,4'-diaminodiphenyl ether. After reacting in an ice bath for 4h, stir at room temperature for 12h. After the reaction is completed, a light yellow liquid is obtained;

[0036] Q2: 3 g of hydroxyl-terminated polycaprolactone with an average molecular weight of 2000 Da was added to 50 mL of N, N-dimethylacetamide, heated at 80 ° C under a nitrogen atmosphere, and then 0.75 g of diphenylmethane diisocyanate and 0.023 g of dibutyltin dilaurate were added. After reacting for 24 hours, a prepolymer was obtained. Then 0.36 g of isophthalic acid hydrazide was added to the prepolymer, and the reaction was carried out under a nitrogen atmosphere for 24 hours. After the reaction, a polymer substance was obtained;

[0037] Q3: Add 8 mL of acrylic acid to 22.5 mL of distilled water, stir, then add 0.027 g of ammonium persulfate and 0.5 mL of poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate, stir evenly, add 0.11 g of sodium sulfite, heat at 45 °C for 15 min to obtain a gel;

[0038] Q4: Add 0.48 g of terephthalaldehyde to 35 mL of N,N-dimethylacetamide, add 2.1 g of light yellow liquid and 19.5 g of polymer under stirring, heat and stir at 100°C for 12 hours to obtain a mixed solution, stir the mixed solution with 0.4 g of gel for 2 hours to obtain a conductive modifier.

[0039] This embodiment discloses a method for preparing an interface stabilizer, comprising the following steps:

[0040] S1: Add 1 g of cyanuric chloride to a container containing 20 mL of tetrahydrofuran, stir to dissolve, dissolve 0.48 g of diethylamine in 20 mL of tetrahydrofuran, slowly dropwise add to the container, stir to mix, add 1.95 g of potassium carbonate, react at -10°C for 2 h, add distilled water to quench the reaction, extract with ethyl acetate, dry with anhydrous magnesium sulfate, and purify to obtain intermediate 1;

[0041] S2: 1 g of 4,7-dichloroquinoline and 11 g of 2-methylpiperazine were added to 22.5 mL of anhydrous ethanol, stirred and dissolved, and then heated to reflux at 80°C for 6 h. After the reflux, the mixture was distilled under reduced pressure and purified by adding silica gel powder. The eluent was a mixed solution of dichloromethane and methanol in a volume ratio of 10:1 to obtain intermediate 2.

[0042] S3: 1.32 g of intermediate 2 was added to 0.47 g of 1,4-dioxane, and after mixing evenly, 0.65 g of potassium carbonate and 0.9 g of intermediate 1 were added, and the mixture was stirred at room temperature for 16 h. The mixture was filtered, and distilled under reduced pressure. After purification, silica gel powder was added. The eluent was a mixed solution of ethyl acetate and petroleum ether in a volume ratio of 5:1 to obtain an interfacial stabilizer.

[0043] The present embodiment discloses a negative electrode sheet for a new energy battery. The negative electrode sheet for the new energy battery is composed of aluminum foil and negative electrode slurry. The negative electrode slurry is composed of the following components in parts by weight: 45 parts of lithium titanate, 8 parts of a conductive modifier, 8.5 parts of an interface stabilizer, 3.5 parts of polyvinylidene fluoride, and 2.5 parts of N-methylpyrrolidone.

[0044] This embodiment discloses a method for preparing a negative electrode sheet for a new energy battery, comprising the following steps:

[0045] Step 1: Add polyvinylidene fluoride to N-methylpyrrolidone, then add lithium titanate, and after magnetic stirring for 5 hours, add a conductive modifier and an interface stabilizer, and continue magnetic stirring for 12 hours to obtain a negative electrode slurry;

[0046] Step 2: The negative electrode slurry is evenly coated on the aluminum foil, and vacuum dried at 80°C and 0.2MPa for 12 hours to obtain a negative electrode sheet.

[0047] Example 2: This example discloses a method for preparing a conductive modifier, comprising the following steps:

[0048] Q1: Add 0.93g of 4,4'-(hexafluoroisopropylene) diphthalic anhydride to a container containing 7.5mL of N,N-dimethylacetamide, stir to dissolve, and then slowly add dropwise to a 6mL of N,N-dimethylacetamide solution containing 0.5g of 4,4'-diaminodiphenyl ether. After reacting in an ice bath for 4h, stir at room temperature for 12h. After the reaction is completed, a light yellow liquid is obtained;

[0049] Q2: 2 g of hydroxyl-terminated polycaprolactone with an average molecular weight of 2000 Da was added to 50 mL of N,N-dimethylacetamide, heated at 80°C under a nitrogen atmosphere, and then 1 g of diphenylmethane diisocyanate and 0.025 g of dibutyltin dilaurate were added. After reacting for 24 hours, a prepolymer was obtained. Then 0.24 g of isophthalic acid hydrazide was added to the prepolymer, and the reaction was carried out under a nitrogen atmosphere for 24 hours. After the reaction was completed, a polymer substance was obtained;

[0050] Q3: Add 6 mL of acrylic acid to 20 mL of distilled water, stir, then add 0.025 g of ammonium persulfate and 0.4 mL of poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate, stir evenly, add 0.092 g of sodium sulfite, heat at 45 °C for 15 min to obtain a gel;

[0051] Q4: Add 0.32 g of terephthalaldehyde to 25 mL of N,N-dimethylacetamide, add 1.4 g of light yellow liquid and 12.9 g of polymer under stirring, heat and stir at 100°C for 12 hours to obtain a mixed solution, stir the mixed solution with 0.3 g of gel for 2 hours to obtain a conductive modifier.

[0052] This embodiment discloses a method for preparing an interface stabilizer, comprising the following steps:

[0053] S1: Add 1 g of cyanuric chloride to a container containing 20 mL of tetrahydrofuran, stir to dissolve, dissolve 0.438 g of diethylamine in 20 mL of tetrahydrofuran, slowly dropwise add to the container, stir to mix, add 1.8 g of potassium carbonate, react at -10°C for 2 h, add distilled water to quench the reaction, extract with ethyl acetate, dry with anhydrous magnesium sulfate, and purify to obtain intermediate 1;

[0054] S2: 1 g of 4,7-dichloroquinoline and 10 g of 2-methylpiperazine were added to 25 mL of anhydrous ethanol, stirred to dissolve, and then heated to reflux at 80°C for 6 h. After the reflux, the mixture was distilled under reduced pressure, and purified by adding silica gel powder. The eluent was a mixed solution of dichloromethane and methanol in a volume ratio of 10:1, to obtain intermediate 2;

[0055] S3: Add 1.05 g of intermediate 2 to 0.38 g of 1,4-dioxane, mix well, add 0.65 g of potassium carbonate and 0.75 g of intermediate 1, stir at room temperature for 16 h, filter, distill under reduced pressure, add silica gel powder for purification, and use a mixed solution of ethyl acetate and petroleum ether in a volume ratio of 5:1 as the eluent to obtain an interfacial stabilizer.

[0056] The present embodiment discloses a negative electrode sheet for a new energy battery. The negative electrode sheet for a new energy battery is composed of aluminum foil and negative electrode slurry. The negative electrode slurry is composed of the following components in parts by weight: 42 parts of lithium titanate, 6 parts of a conductive modifier, 5 parts of an interface stabilizer, 2 parts of polyvinylidene fluoride, and 1 part of N-methylpyrrolidone.

[0057] This embodiment discloses a method for preparing a negative electrode sheet for a new energy battery, comprising the following steps:

[0058] Step 1: Add polyvinylidene fluoride to N-methylpyrrolidone, then add lithium titanate, and after magnetic stirring for 5 hours, add a conductive modifier and an interface stabilizer, and continue magnetic stirring for 12 hours to obtain a negative electrode slurry;

[0059] Step 2: The negative electrode slurry is evenly coated on the aluminum foil, and vacuum dried at 80°C and 0.2MPa for 12 hours to obtain a negative electrode sheet.

[0060] Example 3: This example discloses a method for preparing a conductive modifier, comprising the following steps:

[0061] Q1: Add 1.85g of 4,4'-(hexafluoroisopropylene) diphthalic anhydride to a container containing 7.5mL of N,N-dimethylacetamide, stir to dissolve, and then slowly drop into a 6mL of N,N-dimethylacetamide solution containing 1g of 4,4'-diaminodiphenyl ether. After reacting in an ice bath for 4h, stir at room temperature for 12h. After the reaction is completed, a light yellow liquid is obtained;

[0062] Q2: 4 g of hydroxyl-terminated polycaprolactone with an average molecular weight of 2000 Da was added to 50 mL of N, N-dimethylacetamide, heated at 80 ° C under a nitrogen atmosphere, and then 0.5 g of diphenylmethane diisocyanate and 0.02 g of dibutyltin dilaurate were added. After reacting for 24 hours, a prepolymer was obtained. Then 0.49 g of isophthalic acid hydrazide was added to the prepolymer, and the reaction was carried out under a nitrogen atmosphere for 24 hours. After the reaction, a polymer substance was obtained;

[0063] Q3: Add 10 mL of acrylic acid to 25 mL of distilled water, stir, then add 0.03 g of ammonium persulfate and 0.6 mL of poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate, stir evenly, add 0.128 g of sodium sulfite, heat at 45 °C for 15 min to obtain a gel;

[0064] Q4: Add 0.64 g of terephthalaldehyde to 50 mL of N,N-dimethylacetamide, add 2.8 g of light yellow liquid and 25.8 g of polymer under stirring, heat and stir at 100°C for 12 hours to obtain a mixed solution, stir the mixed solution with 0.5 g of gel for 2 hours to obtain a conductive modifier.

[0065] This embodiment discloses a method for preparing an interface stabilizer, comprising the following steps:

[0066] S1: Add 1 g of cyanuric chloride to a container containing 20 mL of tetrahydrofuran, stir to dissolve, dissolve 0.53 g of diethylamine in 20 mL of tetrahydrofuran, slowly dropwise add to the container, stir to mix, add 2.1 g of potassium carbonate, react at -10°C for 2 h, add distilled water to quench the reaction, extract with ethyl acetate, dry with anhydrous magnesium sulfate, and purify to obtain intermediate 1;

[0067] S2: 1 g of 4,7-dichloroquinoline and 12 g of 2-methylpiperazine were added to 20 mL of anhydrous ethanol, stirred to dissolve, and then heated to reflux at 80°C for 6 h. After the reflux, the mixture was distilled under reduced pressure, and purified by adding silica gel powder. The eluent was a mixed solution of dichloromethane and methanol in a volume ratio of 10:1, to obtain intermediate 2;

[0068] S3: 1.57 g of intermediate 2 was added to 0.56 g of 1,4-dioxane, and after mixing evenly, 0.65 g of potassium carbonate and 1 g of intermediate 1 were added, and the mixture was stirred at room temperature for 16 h. The mixture was filtered, and distilled under reduced pressure. After purification, silica gel powder was added. The eluent was a mixed solution of ethyl acetate and petroleum ether in a volume ratio of 5:1 to obtain an interfacial stabilizer.

[0069] The present embodiment discloses a negative electrode sheet for a new energy battery. The negative electrode sheet for a new energy battery is composed of aluminum foil and negative electrode slurry. The negative electrode slurry is composed of the following components in parts by weight: 48 parts of lithium titanate, 10 parts of a conductive modifier, 12 parts of an interface stabilizer, 5 parts of polyvinylidene fluoride, and 4 parts of N-methylpyrrolidone.

[0070] This embodiment discloses a method for preparing a negative electrode sheet for a new energy battery, comprising the following steps:

[0071] Step 1: Add polyvinylidene fluoride to N-methylpyrrolidone, then add lithium titanate, and after magnetic stirring for 5 hours, add a conductive modifier and an interface stabilizer, and continue magnetic stirring for 12 hours to obtain a negative electrode slurry;

[0072] Step 2: The negative electrode slurry is evenly coated on the aluminum foil, and vacuum dried at 80°C and 0.2MPa for 12 hours to obtain a negative electrode sheet.

[0073] Example 4: This example discloses a method for preparing a conductive modifier, comprising the following steps:

[0074] Q1: Add 1.15g of 4,4'-(hexafluoroisopropylene) diphthalic anhydride to a container containing 7.5mL of N,N-dimethylacetamide, stir to dissolve, and then slowly add dropwise to a 6mL of N,N-dimethylacetamide solution containing 0.6g of 4,4'-diaminodiphenyl ether. After reacting in an ice bath for 4h, stir at room temperature for 12h. After the reaction is completed, a light yellow liquid is obtained;

[0075] Q2: 2.5 g of hydroxyl-terminated polycaprolactone with an average molecular weight of 2000 Da was added to 50 mL of N,N-dimethylacetamide, heated at 80°C under a nitrogen atmosphere, and then 0.6 g of diphenylmethane diisocyanate and 0.021 g of dibutyltin dilaurate were added. After reacting for 24 hours, a prepolymer was obtained. Then 0.28 g of isophthalic acid hydrazide was added to the prepolymer, and the reaction was carried out under a nitrogen atmosphere for 24 hours. After the reaction was completed, a polymer substance was obtained;

[0076] Q3: Add 7 mL of acrylic acid to 22 mL of distilled water, stir, then add 0.026 g of ammonium persulfate and 0.45 mL of poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate, stir evenly, add 0.098 g of sodium sulfite, heat at 45 °C for 15 min to obtain a gel;

[0077] Q4: Add 0.4 g of terephthalaldehyde to 28 mL of N,N-dimethylacetamide, add 1.8 g of light yellow liquid and 14.2 g of polymer under stirring, heat and stir at 100°C for 12 hours to obtain a mixed solution, stir the mixed solution with 0.35 g of gel for 2 hours to obtain a conductive modifier.

[0078] This embodiment discloses a method for preparing an interface stabilizer, comprising the following steps:

[0079] S1: Add 1 g of cyanuric chloride to a container containing 20 mL of tetrahydrofuran, stir to dissolve, dissolve 0.45 g of diethylamine in 20 mL of tetrahydrofuran, slowly dropwise add to the container, stir to mix, add 1.9 g of potassium carbonate, react at -10°C for 2 h, add distilled water to quench the reaction, extract with ethyl acetate, dry with anhydrous magnesium sulfate, and purify to obtain intermediate 1;

[0080] S2: 1 g of 4,7-dichloroquinoline and 12.5 g of 2-methylpiperazine were added to 21 mL of anhydrous ethanol, stirred to dissolve, and then heated to reflux at 80°C for 6 h. After the reflux, the mixture was distilled under reduced pressure and purified by adding silica gel powder. The eluent was a mixed solution of dichloromethane and methanol in a volume ratio of 10:1 to obtain intermediate 2.

[0081] S3: Add 1.21 g of intermediate 2 to 0.42 g of 1,4-dioxane, mix well, add 0.65 g of potassium carbonate and 0.8 g of intermediate 1, stir at room temperature for 16 h, filter, distill under reduced pressure, add silica gel powder for purification, and use a mixed solution of ethyl acetate and petroleum ether in a volume ratio of 5:1 as the eluent to obtain an interfacial stabilizer.

[0082] The present embodiment discloses a negative electrode sheet for a new energy battery. The negative electrode sheet for the new energy battery is composed of aluminum foil and negative electrode slurry. The negative electrode slurry is composed of the following components in parts by weight: 43 parts of lithium titanate, 7 parts of a conductive modifier, 7 parts of an interface stabilizer, 4 parts of polyvinylidene fluoride, and 2 parts of N-methylpyrrolidone.

[0083] This embodiment discloses a method for preparing a negative electrode sheet for a new energy battery, comprising the following steps:

[0084] Step 1: Add polyvinylidene fluoride to N-methylpyrrolidone, then add lithium titanate, and after magnetic stirring for 5 hours, add a conductive modifier and an interface stabilizer, and continue magnetic stirring for 12 hours to obtain a negative electrode slurry;

[0085] Step 2: The negative electrode slurry is evenly coated on the aluminum foil, and vacuum dried at 80°C and 0.2MPa for 12 hours to obtain a negative electrode sheet.

[0086] Example 5: This example discloses a method for preparing a conductive modifier, comprising the following steps:

[0087] Q1: Add 1.57g of 4,4'-(hexafluoroisopropylene) diphthalic anhydride to a container containing 7.5mL of N,N-dimethylacetamide, stir to dissolve, and then slowly drop into a 6mL of N,N-dimethylacetamide solution containing 0.8g of 4,4'-diaminodiphenyl ether. After reacting in an ice bath for 4h, stir at room temperature for 12h. After the reaction is completed, a light yellow liquid is obtained;

[0088] Q2: 3.5 g of hydroxyl-terminated polycaprolactone with an average molecular weight of 2000 Da was added to 50 mL of N, N-dimethylacetamide, heated at 80 ° C under a nitrogen atmosphere, and then 0.8 g of diphenylmethane diisocyanate and 0.024 g of dibutyltin dilaurate were added. After reacting for 24 hours, a prepolymer was obtained. Then 0.41 g of isophthalic acid hydrazide was added to the prepolymer, and the reaction was carried out under a nitrogen atmosphere for 24 hours. After the reaction, a polymer substance was obtained;

[0089] Q3: Add 9 mL of acrylic acid to 24 mL of distilled water, stir, then add 0.028 g of ammonium persulfate and 0.55 mL of poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate, stir evenly, add 0.114 g of sodium sulfite, heat at 45 °C for 15 min to obtain a gel;

[0090] Q4: Add 0.58 g of terephthalaldehyde to 47 mL of N,N-dimethylacetamide, add 2.4 g of light yellow liquid and 21.7 g of polymer under stirring, heat and stir at 100°C for 12 hours to obtain a mixed solution, stir the mixed solution with 0.45 g of gel for 2 hours to obtain a conductive modifier.

[0091] This embodiment discloses a method for preparing an interface stabilizer, comprising the following steps:

[0092] S1: Add 1 g of cyanuric chloride to a container containing 20 mL of tetrahydrofuran, stir to dissolve, dissolve 0.51 g of diethylamine in 20 mL of tetrahydrofuran, slowly dropwise add to the container, stir to mix, add 2 g of potassium carbonate, react at -10°C for 2 h, add distilled water to quench the reaction, extract with ethyl acetate, dry with anhydrous magnesium sulfate, and purify to obtain intermediate 1;

[0093] S2: 1 g of 4,7-dichloroquinoline and 11.5 g of 2-methylpiperazine were added to 24 mL of anhydrous ethanol, stirred and dissolved, and then heated to reflux at 80°C for 6 h. After the reflux, the mixture was distilled under reduced pressure and purified by adding silica gel powder. The eluent was a mixed solution of dichloromethane and methanol in a volume ratio of 10:1 to obtain intermediate 2.

[0094] S3: 1.48 g of intermediate 2 was added to 0.52 g of 1,4-dioxane, and after mixing evenly, 0.65 g of potassium carbonate and 0.83 g of intermediate 1 were added, and the mixture was stirred at room temperature for 16 h. The mixture was filtered, and distilled under reduced pressure. After purification, silica gel powder was added. The eluent was a mixed solution of ethyl acetate and petroleum ether in a volume ratio of 5:1 to obtain an interfacial stabilizer.

[0095] The present embodiment discloses a negative electrode sheet for a new energy battery. The negative electrode sheet for the new energy battery is composed of aluminum foil and negative electrode slurry. The negative electrode slurry is composed of the following components in parts by weight: 47 parts of lithium titanate, 9 parts of a conductive modifier, 10 parts of an interface stabilizer, 3 parts of polyvinylidene fluoride, and 3 parts of N-methylpyrrolidone.

[0096] This embodiment discloses a method for preparing a negative electrode sheet for a new energy battery, comprising the following steps:

[0097] Step 1: Add polyvinylidene fluoride to N-methylpyrrolidone, then add lithium titanate, and after magnetic stirring for 5 hours, add a conductive modifier and an interface stabilizer, and continue magnetic stirring for 12 hours to obtain a negative electrode slurry;

[0098] Step 2: The negative electrode slurry is evenly coated on the aluminum foil, and vacuum dried at 80°C and 0.2MPa for 12 hours to obtain a negative electrode sheet.

[0099] Comparative Example 1: Compared with Example 1, in the process of preparing the conductive modifier in Comparative Example 1, no poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate is added, and other conditions remain unchanged.

[0100] Comparative Example 2: Compared with Example 1, in the process of preparing the interface stabilizer in Comparative Example 2, no cyanuric chloride is added, and other conditions remain unchanged.

[0101] Comparative Example 3: Compared with Example 1, in the process of preparing the negative electrode sheet in Comparative Example 3, no conductive modifier is added, and other conditions remain unchanged.

[0102] Comparative Example 4: Compared with Example 1, in Comparative Example 4, during the process of preparing the negative electrode sheet, no interface stabilizer is added, and other conditions remain unchanged.

[0103] Experimental example: The performance of the samples was tested according to GB / T 44027.1-2024. The test results are shown in Table 1:

[0104] Table 1

[0105] project <![CDATA[Initial discharge specific capacity / mAh·g -1 > First coulombic efficiency / % Discharge capacity retention rate / % Example 1 198.44 93.62 88.63 Example 2 197.36 93.16 88.39 Example 3 197.02 92.93 88.31 Example 4 196.86 92.44 88.11 Example 5 197.24 92.16 87.94 Comparative Example 1 185.56 88.49 81.45 Comparative Example 2 186.34 88.37 81.62 Comparative Example 3 183.17 87.64 80.29 Comparative Example 4 182.03 87.46 80.34

[0106] The first discharge specific capacity reflects the energy storage capacity and discharge performance of the negative electrode material. A high first discharge specific capacity means that the negative electrode material can store and release more energy during the initial charge and discharge process, thereby improving the overall performance of the battery. The first coulombic efficiency reflects the internal loss of the battery. A high first coulombic efficiency means that the negative electrode material has lower internal loss during the first charge and discharge process, and can more effectively utilize the input electrical energy for energy storage and release. The discharge capacity retention rate is used to evaluate the cycle stability and life of the negative electrode material. A high discharge capacity retention rate means that the negative electrode material can still maintain good energy storage capacity after multiple charge and discharge cycles, thereby extending the service life of the battery. As can be seen from the test results in Table 1, the negative electrode sheets prepared in Examples 1-5 of the present invention have excellent energy storage capacity, low internal loss, and excellent cycle performance. From the comparison between Comparative Example 1 and Examples 1-5, it can be seen that the addition of poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate can effectively improve the energy storage capacity and cycle performance of the negative electrode sheet and reduce the internal loss of the battery; from the comparison between Comparative Example 2 and Examples 1-5, it can be seen that the addition of cyanuric chloride can effectively improve the energy storage capacity and cycle performance of the negative electrode sheet and reduce the internal loss of the battery; from the comparison between Comparative Example 3 and Examples 1-5, it can be seen that the addition of a conductive modifier can effectively improve the energy storage capacity and cycle performance of the negative electrode sheet and reduce the internal loss of the battery; from the comparison between Comparative Example 4 and Examples 1-5, it can be seen that the addition of an interface stabilizer can effectively improve the energy storage capacity and cycle performance of the negative electrode sheet and reduce the internal loss of the battery.

[0107] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

[0108] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A negative electrode sheet for a new energy battery, characterized in that: The negative electrode sheet for new energy batteries is composed of aluminum foil and negative electrode slurry, and the negative electrode slurry is composed of the following components in parts by weight: 42-48 parts of lithium titanate, 6-10 parts of conductive modifier, 5-12 parts of interface stabilizer, 2-5 parts of binder, and 1-4 parts of N-methylpyrrolidone, wherein the conductive modifier is prepared from 4,4'-(hexafluoroisopropylene) diphthalic anhydride, 4,4'-diaminodiphenyl ether, hydroxyl-terminated polycaprolactone, diphenylmethane diisocyanate, isophthalic acid hydrazide, acrylic acid and poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate, and the interface stabilizer is prepared from cyanuric chloride. 、 Diethylamine 、 The invention is prepared by using 4,7-dichloroquinoline and 2-methylpiperazine, and the binder is composed of one or more of polyvinylidene fluoride, sodium polyacrylate, sodium alginate and sodium carboxymethyl cellulose.

2. The negative electrode sheet for new energy batteries according to claim 1, characterized in that: The preparation method of the conductive modifier comprises the following steps: Q1: Add 4,4'-(hexafluoroisopropylene) diphthalic anhydride to a container containing N,N-dimethylacetamide, stir to dissolve, and then slowly add dropwise to the N,N-dimethylacetamide solution containing 4,4'-diaminodiphenyl ether. After reacting in an ice bath, stir and react at room temperature. After the reaction is completed, a light yellow liquid is obtained. Q2: Add hydroxyl-terminated polycaprolactone to N,N-dimethylacetamide, heat under nitrogen atmosphere, then add diphenylmethane diisocyanate and dibutyltin dilaurate to react to obtain a prepolymer, then add isophthalic acid hydrazide to the prepolymer, react under nitrogen atmosphere, and obtain a polymer after the reaction is completed; Q3: Add acrylic acid to distilled water, stir, then add ammonium persulfate and poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate, stir evenly, add sodium sulfite, heat and react to obtain a gel; Q4: Add terephthalaldehyde to N,N-dimethylacetamide, add light yellow liquid and polymer substance under stirring condition, heat and stir to obtain a mixed solution, stir and mix the mixed solution with gel to obtain a conductive modifier.

3. The negative electrode sheet for new energy batteries according to claim 2, characterized in that: In Q1, the molar ratio of 4,4'-(hexafluoroisopropylene) diphthalic anhydride and 4,4'-diaminodiphenyl ether is (0.25-0.5):(0.3-0.6), the ice bath reaction time is 4-6 hours, and the stirring reaction time is 10-12 hours; in Q2, the average molecular weight of the hydroxyl-terminated polycaprolactone is 2000Da, and the molar ratio of the hydroxyl-terminated polycaprolactone, diphenylmethane diisocyanate, dibutyltin dilaurate and isophthalic acid hydrazide is (0.5-1):(1-2):(0.016-0.02):(0.62-1.25), the heating temperature is 80-90°C, the reaction time is 20-24 hours, and the reaction time under nitrogen atmosphere is 22-24 hours.

4. The negative electrode sheet for new energy batteries according to claim 2, characterized in that: In the Q3, the usage ratio of acrylic acid, distilled water, ammonium persulfate, poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate and sodium sulfite is (6-10) mL: (20-25) mL: (0.025-0.03) g: (0.4-0.6) mL: (0.092-0.128) g, the heating reaction temperature is 40-50°C, and the reaction time is 10-15 min. In the Q4, the usage ratio of terephthalaldehyde, N,N-dimethylacetamide, light yellow liquid, polymer substance and gel is (0.32-0.64) g: (25-50) mL: (1.4-2.8) g: (12.9-25.8) g: (0.3-0.5) g, the heating and stirring temperature is 90-110°C, the stirring time is 10-12 h, and the stirring and mixing time is 2-3 h.

5. The negative electrode sheet for new energy batteries according to claim 1, characterized in that: The preparation method of the interface stabilizer comprises the following steps: S1: Add cyanuric chloride to a container containing tetrahydrofuran, stir to dissolve, dissolve diethylamine in tetrahydrofuran, slowly add it dropwise to the container, stir to mix, add potassium carbonate, react at low temperature, add distilled water to quench the reaction, extract, dry, and purify to obtain intermediate 1; S2: Add 4,7-dichloroquinoline and 2-methylpiperazine to anhydrous ethanol, stir to dissolve, heat to reflux, and after the reflux is completed, perform vacuum distillation and purification to obtain intermediate 2; S3: Add intermediate 2 to 1,4-dioxane, mix well, add potassium carbonate and intermediate 1, stir at room temperature, filter, distill under reduced pressure, and purify to obtain an interfacial stabilizer.

6. The negative electrode sheet for new energy batteries according to claim 5, characterized in that: In the S1, the usage ratio of cyanuric chloride, diethylamine and potassium carbonate is 1g: (0.438-0.53)g: (1.8-2.1)g, the low-temperature reaction temperature is -10 to -15°C, the time is 1-2h, extraction is performed with ethyl acetate, and drying is performed with anhydrous magnesium sulfate.

7. The negative electrode sheet for new energy batteries according to claim 5, characterized in that: In the S2, the dosage ratio of 4,7-dichloroquinoline, 2-methylpiperazine and anhydrous ethanol is 1g:(10-12.5)g:(20-25)mL, the heating reflux temperature is 70-80°C, the time is 5-7h, and the purification is carried out after adding silica gel powder. The eluent is a mixed solution of dichloromethane and methanol in a volume ratio of 10:

1.

8. The negative electrode sheet for new energy batteries according to claim 5, characterized in that: In S3, the molar ratio of intermediate 2, 1,4-dioxane and intermediate 1 is (0.8-1.2):(0.8-1.2):(0.9-1.2), the stirring time at room temperature is 12-16 hours, and purification is carried out after adding silica gel powder. The eluent is a mixed solution of ethyl acetate and petroleum ether in a volume ratio of 5:

1.

9. The method for preparing a negative electrode sheet for a new energy battery according to any one of claims 1 to 8, characterized in that: The following steps are involved: Step 1: Add a binder to N-methylpyrrolidone, then add lithium titanate, add a conductive modifier and an interface stabilizer after magnetic stirring, and continue magnetic stirring to obtain a negative electrode slurry; Step 2: Evenly coat the negative electrode slurry on the aluminum foil and vacuum dry it to obtain a negative electrode sheet.

10. The method for preparing a negative electrode sheet for a new energy battery according to claim 9, characterized in that: In the step 1, the magnetic stirring time is 3-5 hours, and the continued magnetic stirring time is 10-12 hours; in the step 2, the vacuum drying temperature is 80-90° C., the vacuum degree is 0.1-0.2 MPa, and the drying time is 10-12 hours.

Citation Information

Patent Citations

  • Modified porous graphene, modified porous graphene negative electrode plate and preparation method thereof

    CN106848312A

  • PEDOT: PSS / CMC composite binder and preparation method and application thereof

    CN110890545A

  • Lithium battery composite electrode pole piece and preparation method and application thereof

    CN111933940A

  • Composition for forming secondary battery electrode, electrode for secondary battery, and secondary battery

    JP2014225446A

  • Stretchable current collector and lithium secondary battery including the same

    US20230387419A1